THE RELATIONSHIP BETWEEN ETHNICITY DIFFERENCES AND LANGUAGE LEARNERS’ WILLINGNESS TO COMMUNICATE IN CLASSROOM DISCUSSION - Ruri Ariati; Bambang Suwarno (Universitas Negeri Padang, 2017)
Willingnesstocommunicate(WTC) is defined as the intention to communicate given a choice, continues to establish itself as a determining construct in bringing about success or failure in learning a foreign language (Dӧrnyei,2005,Peng&Woodrow,2010). One of the factors affected it was cultural diversities from varies ethnics. Hence, learners’ ethnicity in willingness to communicate is a necessity that has to be considered in language education in multilingual context. In this study, the researchers investigated whether there is any statistically significant relationship between learners’ ethnicity and willingness to communicate in classroom discussion of graduate students of Universitas Negeri Padang that focused on minority and majority group. To collect the data, the questionnaire of willingness to communicate was distributed to the participants that consist of 38 graduate students of English Department of Universitas Negeri Padang. The quantitative data gathered through these instruments were analyzed to determine the degree of correlation between these two variables. Besides, individual semi-structured interviews with some of the participants were used to obtain supportive data. The results of correlational analyses revealed that there was a strong relationship between learners’ Willingness to Communicate and their ethnicity differences. So it can be concluded that a significant relationship between learner ethnicity and willingness to communicate can be seen in classroom discussion that the majority ethnic dominate and have willingness to express their ideas rather than minority group that come from minority ethnic in classroom discussion.